Association Between Opioid Use Disorder and Seizure Incidents Among Alcohol Use Disorder Patients - Hiroko Furo; Ankita Podichetty; Marisa Whitted; Yi Yuan Zhou; Francis Torres; Bradley B. Brimhall (SAGE Publishing, 2023)
Many previous studies have discussed an association between alcohol use disorder (AUD) and seizure incidents. There are also case reports of seizures during opioid withdrawals. Therefore, it is possible that AUD patients may have a higher risk of seizures if they also have opioid use disorder (OUD). However, it remains unproven whether AUD patients with a dual diagnosis of OUD have higher seizure incidents, to our knowledge. This study explored seizure incidents among the patients with a dual diagnosis of AUD and OUD as well as seizures among AUD only or OUD only patients. This study utilized de-identified data from 30 777 928 hospital inpatient encounters at 948 healthcare systems over 4 years (9/1/2018-8/31/2022) from the Vizient ® Clinical Database for this study. Applying the International Classification of Diseases 10th Revision (ICD-10) diagnostic codes, AUD (1 953 575), OUD (768 982), and seizure (1 209 471) encounters were retrieved from the database to examine the effects of OUD on seizure incidence among AUD patients. This study also stratified patient encounters for demographic factors such as gender, age, and race, as well as the Vizient-categorized primary payer. Greatest gender differences were identified among AUD followed by OUD, and seizure patient groups. The mean age for seizure incidents was 57.6 years, while that of AUD was 54.7 years, and OUD 48.9 years. The greatest proportion of patients in all 3 groups were White, followed by Black, with Medicare being the most common primary payer in all 3 categories. Seizure incidents were statistically more common ( P  < .001, chi-square) in patients with a dual diagnosis of AUD and OUD (8.07%) compared to those with AUD only (7.55%). The patients with the dual diagnosis had a higher odd ratio than those with AUD only or OUD only. These findings across more than 900 health systems provide a greater understanding of seizure risks. Consequently, this information may help in triaging AUD and OUD patients in certain higher-risk demographic groups.